Animações procedimentais em saúde: Proposta de Metodologia de Design para a Universidade Aberta do SUS (UNA-SUS/UFMA) | Procedural animations in health: Proposal of Design Methodology for the Open University of the Brazilian Unified Health System of the Federal University of Maranhão - Spinillo, Carla G.; Oliveira, Ana Emilia F.; Mazza, Larissa U.; Castro Lima, Camila S. de; Assis, Katherine Marjorie de (InfoDesign, 2020)
Animações instrucionais são recursos efetivos no aprendizado de conteúdos. Todavia, seu desenvolvimento demanda investigação científica para promover eficácia comunicativa considerando aspectos pedagógicos e de design da informação. Consderando isto, foi proposta uma metodologia para desenvolvimento de Sequências Pictóricas de Procedimentos Animadas -SPPAs na área de saúde para a UNA-SUS/UFMA - Universidade Aberta do SUS da Universidade Federal do Maranhão. A metodologia se fundamentou nos resultados de um Estudo da Representação Gráfico-informacional de SPPAs na área médica em uma amostra de 100 animações juntamente com Análise de contexto com os coordenadores da e alunos da UNA-SUS/UFMA. A Metodologia proposta consta de três fases: (a)Decupagem: definição de conteúdo; resultando em um roteiro; (b) Representação: visualização dos conteúdos; resultando em um storyboard visual; e (c) Finalização: edição final e veiculação da animação. A metodologia foi avaliada positivamente através de grupo focal com desenvolvedores. ***** Procedural animations are important resources in learning content and are employed by the Open University of the Brazilian Unified Health System of the Federal University of Maranhão in its courses for health professionals. However, the development of animations is carried out unsystematically and neglecting representational aspects of information design. Aiming to contribute to the informaion design process of these animations, a design methodology was proposed for the Open University. This was founded on the results of a study on graphic representation of a sample of 100 animations and on context analysis. This was conducted through semi-structured interviews with coordinators of the intuition and online questionnaire with students. The results indicated deficiencies in the animation sample, especially omission of inventory information and warnings. In the context analysis, the interviewees pointed out the need for a methodology to assist the production of animations. In the questionnaire, the students considered animations important and motivating for their learning. Based upon these results, a methodology consisting of three stages was proposed: (1) Decoupage: definition of the graphic-informational structure of the animation content; (2) Representation: design of information through images and narration/audio; and (3) Finishing: animation editing and closing of file. The methodology was evaluated through a focus group with designers, instructional designers and information technology professionals, who considered it satisfactory and useful. It is concluded that the proposed methodology ensures the systematic inclusion of information design aspects in the production of procedural animations, thus, meeting its objective.